The tainted cup - Bennett, Robert Jackson, 1984- (Bennett, Robert Jackson, 1984- Shadow of the Leviathan, 2024)
"An eccentric detective and her long-suffering assistant untangle a web of magic, deceit, and murder in fantasy reimagining of the classic crime novel"--